2014
DOI: 10.1111/jppi.12073
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Implementing Inclusive Education in Ireland: Principal's Views of the Reasons Students Aged 12+ Are Seeking Enrollment to Special Schools

Abstract: In Ireland, an increasing number of students with special educational needs are leaving mainstream schools and enrolling in special education schools. A comparable context is countries that share an inclusion ideology and are at the implementation stage of inclusive education. The authors sought to investigate the reasons why students aged 12+ are leaving mainstream education and transferring to special schools, and to identify what burden this places on the special schools. Data were obtained from questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 23 publications
4
22
0
2
Order By: Relevance
“…Fifty‐four five‐ to 12‐year‐olds attending mainstream schools and 86 from special schools were assessed using the Strengths and Difficulties questionnaire and the Vineland Adaptive Behaviour Scale. Similarly, Kelly et al's () findings, based on questionnaires completed by 54 headteachers in Ireland, discovered the main reason for the increase in transfer from mainstream to special school of 40% of the 246 pupils older than 12 years over a five‐year period: the failure of mainstream schools to meet their academic, social, emotional and behavioural needs and lack of access to health resources. Indeed Hornby () suggested that placement in a special class or special school is more likely to lead to a sense of belonging for children with special educational needs because they are comfortable with peers who have similar disabilities.…”
Section: Discussionmentioning
confidence: 92%
“…Fifty‐four five‐ to 12‐year‐olds attending mainstream schools and 86 from special schools were assessed using the Strengths and Difficulties questionnaire and the Vineland Adaptive Behaviour Scale. Similarly, Kelly et al's () findings, based on questionnaires completed by 54 headteachers in Ireland, discovered the main reason for the increase in transfer from mainstream to special school of 40% of the 246 pupils older than 12 years over a five‐year period: the failure of mainstream schools to meet their academic, social, emotional and behavioural needs and lack of access to health resources. Indeed Hornby () suggested that placement in a special class or special school is more likely to lead to a sense of belonging for children with special educational needs because they are comfortable with peers who have similar disabilities.…”
Section: Discussionmentioning
confidence: 92%
“…La principal razón que se esgrime está en el fracaso de las escuelas regulares para satisfacer sus necesidades de recursos académicos, sociales, emocionales, de comportamiento y de acceso a la salud. La experiencia de educación inclusiva en Irlanda es similar a la de los países que todavía luchan con la introducción de prácticas de inclusión en medio de restricciones socioeconómicas y educativas de recursos (Kelly et al, 2014), tal como se ha descrito en Chile.…”
Section: Discussionunclassified
“…Entre sus resultados, se señala que "algunos de los factores que inciden en que no se dé una completa atención son: motivación de los docentes, exigencias del colegio y de los padres, falta de evaluación por parte de la institución al proyecto (…)" (Arias et al, 2005: 51). Existen diferentes miradas sobre sus resultados, por una parte, algunos autores defienden sus efectos positivos (Thomas, 1997;De Schauwer et al, 2009), otros enfatizan en las múltiples complejidades en su implementación (Clark et al, 1999;Norwich y Kelly, 2004) o la falta de evidencia sobre esta (Lindsay, 2007;Kelly et al, 2014).…”
Section: Aspectos Clave De La Inclusión Escolarunclassified
“…Responding to this matter, currently Surabaya City Government has organized Retrieval Remedial (RR) program or commonly known as special service class (KLK), which is program aimed at recruiting or recalling compulsory school age children who have not or no school to get education in school. Students leave public schools to attend special service schools because of the limited school to meet their academic, social, emotional, behavioral, and access needs 7 . Several obstacles in the implementation of inclusive education such as the need for collaboration in planning time of implementation, availability of diverse resources, and the existence of a professional learning community 8 .…”
Section: Introductionmentioning
confidence: 99%